1996
DOI: 10.1128/aem.62.9.3399-3404.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of experimentally induced, nonaflatoxigenic variant strains of Aspergillus parasiticus

Abstract: Six previously isolated, nonaflatoxigenic variants of Aspergillus parasiticus, designated sec mutants, were characterized morphologically by electron microscopy, biochemically by biotransformation studies with an aflatoxin precursor, and genetically by Northern (RNA) hybridization analysis of aflatoxin biosynthetic gene transcripts. Scanning electron micrographs clearly demonstrated that compared with the parental sec ؉ forms, the variant sec forms had an abundance of vegetative mycelia, orders of magnitude re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…At 200 ppm, the inhibition of citrinin production is relatively greater than the inhibition of growth of the fungus, but has not been observed at lower concentrations. It has been suggested that the regulation of toxin synthesis and conidiogenesis may be interlinked (Kale et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…At 200 ppm, the inhibition of citrinin production is relatively greater than the inhibition of growth of the fungus, but has not been observed at lower concentrations. It has been suggested that the regulation of toxin synthesis and conidiogenesis may be interlinked (Kale et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The liquid cultures were incubated at 30°C with constant shaking at 150 RPM. The mycelia were harvested by filtration through miracloth at five different time points (18,24,36,48,72 and 96 h) following inoculation with a conidial suspension. The harvested mycelial samples (wet weight 20 g from wheat bran samples and 10 g from each of the rest of the samples) were mixed and frozen in liquid nitrogen for RNA purification.…”
Section: Fungal Strain Media and Culture Conditionsmentioning
confidence: 99%
“…Secondary metabolism is often correlates with fungal developmental processes such as sporulation and sclerotia formation [16,18,28]. Mutants that are deficient in sporulation are unable to produce aflatoxins [18,28].…”
Section: Genes Putatively Involved In Fungal Development and Sporulationmentioning
confidence: 99%
See 2 more Smart Citations